1996
DOI: 10.1021/es9601604
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Non-extractable Triazine Residues by Enzyme Immunoassay:  Investigation of Model Compounds and Soil Fulvic and Humic Acids

Abstract: 2-Chloro-4-arylamino-6-alkyl-1,3,5-triazines were used as model compounds for non-extractable (bound) triazine residues. They were tested as targets in a competitive enzyme immunoassay with polyclonal and monoclonal antibodies originally raised against atrazine. Cross-reactivities were determined as a measure for the affinity of antibodies toward their respective analytes. 2-Chloro-6-isopropyl derivatives were recognized as well as free atrazine (70-148% cross-reactivity, atrazine ) 100%) with the exception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

1998
1998
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 41 publications
1
13
0
3
Order By: Relevance
“…2) [16,28]. The same Ab binding pattern was observed when FA and HA from soil containing non-extractable residues were investigated by EIA [17].…”
Section: Model Experimentssupporting
confidence: 59%
See 2 more Smart Citations
“…2) [16,28]. The same Ab binding pattern was observed when FA and HA from soil containing non-extractable residues were investigated by EIA [17].…”
Section: Model Experimentssupporting
confidence: 59%
“…Sensitivities are reached down to 10...20 ng/L [15,16], and only small sample volumes (a few milliliters) are necessary. Recently, EIA also have been applied for the determination of non-extractable atrazine residues in soil [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pesticides can be adsorbed or covalently bound to the humic polymer leading to erroneous results. On the other hand, humic substances if present at high concentrations may exhibit nonspecific binding properties in the ELISA [22]. In this study we have used the ELISA developed in our laboratory that has shown a good rep ro d u c i b i l i t y, and the coefficient of variation the IC 50 (concentration reducing the signal to 50% of the control) was less than 10%.…”
Section: Resultsmentioning
confidence: 99%
“…The main part in NOM can be attributed to humic substances (HS) which are divided into fulvic acids (FA) and humic acids (HA) on an operationally-defined basis [2,3]. Different mechanisms for the interaction between NOM and organic contaminants ranging from weak van der Waals forces to covalent binding of the contaminant to the NOM matrix were reported [4][5][6]. Fluorescence spectroscopy is a multidimensional technique with three main independent variables: excitation wavelength λ ex , emission wavelength λ em , and fluorescence decay time τ f .…”
Section: Introductionmentioning
confidence: 99%